2022
DOI: 10.3390/nu14102044
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Digital Food Labels on Healthy Food Choices in Online Grocery Shopping

Abstract: In order to induce the shift in consumer behavior necessary for the mitigation of diet-related diseases, front-of-package labels (FoPL) such as the Nutri-Score that support consumers in their efforts to identify nutritionally valuable products during grocery shopping have been found to be effective; however, they remain non-compulsory in most regions. Counter-intuitively, a similar stream of research on digital web-based FoPL does not yet exist, even though such digital labels hold several advantages over phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Of these articles, 18 met the inclusion criteria and were included for data extraction and evidence synthesis, see Table 2 . Of the eighteen articles, nine studies were randomized controlled trials [ 46 , 49 , 50 , 51 , 52 , 54 , 55 , 56 , 59 ]. Another seven [ 44 , 45 , 47 , 48 , 53 , 57 , 60 ] were observational studies that primarily used quasi-experimental methodologies such as analyzing retail scanner data to follow the behavior of shoppers over time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these articles, 18 met the inclusion criteria and were included for data extraction and evidence synthesis, see Table 2 . Of the eighteen articles, nine studies were randomized controlled trials [ 46 , 49 , 50 , 51 , 52 , 54 , 55 , 56 , 59 ]. Another seven [ 44 , 45 , 47 , 48 , 53 , 57 , 60 ] were observational studies that primarily used quasi-experimental methodologies such as analyzing retail scanner data to follow the behavior of shoppers over time.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies listed in Table 2 were all published between 2015 and 2022. Studies were conducted in Belgium [ 49 ], Denmark [ 56 ], Iceland [ 58 ], Iran [ 59 ], the Netherlands [ 52 ], Spain [ 44 ], the United Kingdom [ 45 , 46 , 48 , 50 , 54 , 55 ], the United States [ 53 , 57 , 60 ], and multiple or unspecified European countries [ 24 , 47 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our review, two articles found differences in purchases [ 48 , 50 ] while one article did not find differences [ 67 ], one article found differences in hypothetical choice [ 61 ] while one article did not find differences [ 52 ]. Regarding research in the literature review, one article did not find the difference [ 41 ] while one article found an increase in purchase [ 42 ], two articles found a difference in hypothetical choice [ 38 , 39 ], and one article found a difference in self-reports [ 40 ] as a function of digitalized interactive FOP food labels. The effects of digitalized technology-enabled FOP food labels and their effects on healthy food-related behavior were the same as in articles identified in this review and previous research [ 15 ] indicating a lack of research regarding digitalized technology-enabled FOP food labels, as shown in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the participants were presented with the FOP food labels and could get more information about the labels or nutritional information by clicking on a specific button. Their results indicate that introducing these FOP food labels did not change overall purchases nor sales of products without “red labels.” Fuchs and colleagues [ 42 ] investigated the effects of interactive FOP food labels on purchase and self-reports of healthy foods in a laboratory-based online grocery store. Specifically, they developed a Google Chrome extension that displayed Nutri-Score for product-specific food products.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation